(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Midgut volvulus is a rare but critical surgical emergency in adults, often leading to diagnostic delays. We present a 22-year-old female with recurrent epigastric pain and bilious vomiting, initially misdiagnosed as gastritis or pancreatitis. Imaging revealed the characteristic “whirlpool sign” on CT and USG, confirming midgut volvulus with an unusual finding of mesenteric lymphadenopathy. This case highlights the pivotal role of radiological imaging in timely diagnosis and underscores mesenteric lymphadenopathy as a potential contributing factor. Early recognition through imaging is crucial in preventing ischemic complications and improving patient outcomes.